Profiles of quality of care among individuals with suicidal behaviors - Fleury, Marie-Josée; Cao, Zhirong; Grenier, Guy; Meng, Xiangfei (Université d'Ottawa | University of Ottawa, 2026)
Abstract Objectives This study identified profiles of individuals with suicidal behaviors (ideations, plans, attempts) and quality of outpatient care received, associated these profiles to the respondents’ sociodemographic and clinical characteristics, and measured outcomes. Methods Using a representative population-based 2015–2016 survey from Quebec (Canada) merged with the province’s health registry (1996–2017), cluster analysis and multinomial logistic regressions were conducted on 569 respondents experiencing suicidal behaviors. Results Among the four identified profiles, 63% had suicidal ideations only (Profile 1, 40% of the cohort; Profile 2, 23%), while 37% reported suicidal plans (mostly Profile 4, 15%) or attempts (mainly Profile 3, 22%) – of Profiles 3 and 4 about one-third reported suicide attempts over their lifetime. Before exhibiting suicidal behaviors, 56% had received low quality of outpatient care – mainly Profiles 1 and 4. Those with the worst social and health conditions, including more serious mental disorders, received the best MH care: Profile 2 patients (suicidal ideations only) received high continuity and regularity of recovery-oriented care; those of Profile 3 (more suicide attempts and unmet needs) received more intensive care. Being older with higher rates of suicidal plans or attempts – and with over 50% of them having mental disorders –, Profile 4 patients received low quality of care and showed the worst outcomes (acute care use, lower quality of life, bad or poor physical/mental health conditions), followed by Profiles 3, 2 and 1. Profile 1 patients also received low quality of care, but showed the best outcomes, probably because of better social and clinical conditions and the fact all of them only had suicidal ideations. Conclusion Quality of care was higher in patients with worse social and health conditions (Profiles 2 and 3). However, findings showed that services could be substantially improved to prevent suicidal behaviors, with outreach interventions significantly strengthened for Profiles 1 and 4. Services could protect patients better against suicidal behaviors and adverse outcomes if they more closely matched their needs and the severity of their conditions. In this sense, Profile 3 and 4 patients would benefit from more continuous follow-up care over time.